Azacitidine and donor lymphocyte infusion for patients with relapsed acute myeloid leukemia and myelodysplastic syndromes after allogeneic hematopoietic stem cell transplantation: A meta-analysis - Li, Xuefeng; Wang, Wen; Zhang, Xin; Wu, Yu (Frontiers in Oncology, 2022)
Background For patients with relapsed acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS) after allogeneic hematopoietic stem cell transplantation (allo-HSCT), azacitidine with donor lymphocyte infusion (DLI) is a feasible option to perform a preemptive or salvage treatment. However, its efficacy lacked comprehensive analysis, and this study aimed to fill this gap. Methods We searched potential studies in PUBMED, EMBASE, and the Cochrane Central Register of Controlled Trials. Thirteen studies involving 811 patients were analyzed. The inverse variance method was used to calculate the pooled proportion and 95% confidence interval (CI). Subgroup analysis was performed to explore the source of heterogeneity. Results The rate of pooled complete remission + partial remission (CR + PR), CR, and 2-year overall survival (OS) were 30% (95% CI: 22%–39%), 21% (95% CI: 16%–28%), and 31% (95% CI: 27%–35%), respectively. The pooled acute graft-versus-host disease (GvHD) and chronic GvHD rates were 15% (95% CI: 9%–23%) and 14% (95% CI: 8%–23%), respectively. Adverse cytogenetics and a higher percentage of bone marrow (BM) blasts at relapse were correlated with worse CR + PR and CR (interaction p < 0.05). Higher 2-year OS was found in patients with lower BM blasts at relapse or a longer time from allo-HSCT to relapse (interaction p < 0.05). Furthermore, the preemptive treatment for molecular relapse/minimal residual disease positivity resulted in much better outcomes than that for hematological relapse, both in terms of CR and 2-year OS (interaction p < 0.001). Conclusion The regimen of azacitidine and DLI could safely improve the outcomes of relapsed AML/MDS after allo-HSCT, especially in those with signs of early relapse. The administration of targeted medicines in azacitidine-based therapies may further improve the outcomes of relapsed AML/MDS.